Writing Argumentative Essay: How Far They Can Go? - Bayu Ramadhan (REiLA : Journal of Research and Innovation in Language, 2019)
Writing is very important for everyone to share their ideas, experiences and their thoughts into the written form. This present study tries to figure out and explore the university students in writing argumentative essay. Therefore, this present conducted a survey research to 21 students who produced 21 argumentative essay from English department in Universitas Lancang Kuning. The survey analysed the Content, Organization, Vocabulary, Grammar, Mechanics In order to answer the research question. The result of the research showed that the students’ ability in argumentative essay was good regarding on the result of the test. This analysis of this present study found that the students’ ability in argumentative essay was categorised in very good level (96,55). This is means that these 21 students can go further on their academic journey regarding English when it needs an argumentative essay in written form.